Inovasi Pemanfaatan Wood Plastic Composite (WPC) sebagai Material Interior Ramah Lingkungan pada Hunian Minimalis - Ratna Hardianningrum; Fitri Dwi Indarti; Anugerah Olivia Azzahra (Jurnal Ragam Pengabdian, 2026)
The development of environmentally friendly building materials is increasingly diverse, one of which is Wood Plastic Composite (WPC) material which is suitable for use in modern minimalist interior design. The concept of modern minimalist interior design focuses on functional efficiency, simplicity and emphasizes bold lines and neutral colors. Wood Plastic Composite (WPC) is a composite material made from wood fiber and recycled plastic that has advantages in terms of durability, aesthetics and environmental sustainability. This study aims to analyze the potential use of Wood Plastic Composite (WPC) as an environmentally friendly interior material in minimalist homes, covering technical aspects, aesthetics, and environmental impacts. The research method used is a descriptive qualitative method including literature studies and analysis of material application in interior elements such as walls, floors, ceilings, and furniture. The results of the study show that Wood Plastic Composite (WPC) has advantages in resistance to moisture, termites and low maintenance compared to natural wood. In addition, the use of Wood Plastic Composite (WPC) material can support the concept of sustainable design because it utilizes recycled materials. Therefore, Wood Plastic Composite (WPC) material has great potential as an alternative environmentally friendly interior material in minimalist homes.